Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan PT. Merdeka Motor Cikarang Utara - Jakaria; Afifah, Nurul (STIE Tri Bhakti, 2024)
This research aims to determine the influence of service quality and product quality on customer satisfaction at PT. Merdeka Motor North Cikarang. This study uses a quantitative approach. The population in this research are customers at PT. Merdeka, North Cikarang. The sample in this study was determined using the Slovin formula with a margin of error of 10%, so that the total data amounted to 97 samples. The analytical methods used are validity, reliability, classical assumption tests, multiple linear regression tests and hypothesis tests. Based on the research results, it shows that: 1) the influence of service quality on customer satisfaction. 2) The Influence of Product Quality on Customer Satisfaction. 3) the influence of service quality and product quality on customer satisfaction. Keywords: Service quality, Product Quality, Customer Satisfaction